성별, 체성분, 체력수준, ACE 유전자 다형성이 다양한 저압·저산소 환경 간 최대하 유산소성 운동능력 차이에 미치는 영향 - 남상석; 문황운; 박훈영; 선우섭 (Exercise science (Seoul, Korea), 2011)
본 연구에서는 고도증가에 따른 최대하 유산소성 운동능력의 변화에 있어서 성별, 체성분, 체력수준, ACE 유전자 다형성의 각 요인에 따른 개별 특이성이 존재하는가를 검토하였다. 연구자료는 일반인 지원자 219명 중 중도탈락자를 제외한 172명의 데이터를 분석에 사용하였다. 대상자들은 모든 측정에 앞서 체성분 검사와 혈액을 통한 ACE 유전자 다형성 검사를 실시하였다. 측정은 해수면 수준부터 5,000m까지 1,000m 단위로 조성된 저압·저산소 환경에서 각각 3일 간격을 두고 실시하였다. 실험 대상자는 각각의 저압·저산소 환경마다 30분간 휴식 후, 안정시 %SpO2와 자전거 에르고미터를 이용한 PWC75%HRmax를 측정하였다. 실험결과 75%HRmax에 해당하는 최대하 유산소성 운동능력은 2,000 m 상당고도에서부터 유의한(p<.05) 감소가 나타나며, 매 1,000 m 씩 고도가 증가할 때마다 지수적으로 감소하는 것을 확인하였다. 또한 고도증가에 따른 최대하 유산소성 운동능력의 감소는 체력수준이 좋은 사람일수록 더 큰 폭으로 나타났으며, 남성이 여성보다 큰 폭으로 나타나지만 남녀의 제지방량을 기준으로 한 상대값의 변화에서는 남녀 간 유의한 성차가 나타나지 않았다. 한편 5,000 m 상당고도에서의 안정시 %SpO2는 여성이 남성보다 크게(p<.05) 감소하였는데 이는 혈액의 산소포화도 변화에 영향을 주는 환기량, 혈액의 산소 친화력, 산소분압 등과 같은 요인들이 극단적인 고도에서 남녀 간 차이를 유발하였기 때문으로 판단된다. 또한 고지대 환경에서의 단발적 운동시 최대하 유산소성 운동능력은 ACE 유전자 다형성 간 차이가 없었다. This study was designed to investigate individual specificity on variation of sex, body composition, physical fitness, ACE gene polymorphism, aerobic exercise capacity depend on altitude. Research subject was 219 ordinary volunteers but 47 ordinary volunteers dropped out. Consequently, 172 ordinary volunteers’data analyzed. Before measurement, body composition test and ACE gene polymorphism test through blood sample carried out, measurement carried out from sea-level to 5,000m in 1,000m unit created hypobaric hypoxia chamber at 3 day intervals. After the subject take a rest in each hypobaric hypoxia environment at 30min, measured %SpO2 and PWC75%HRmax through bike ergometer. As a result, sub-maximal aerobic exercise capacity correspond to 75%HRmax was significant decrease from 2,000 m, as 1,000 m altitude increase, sub-maximal aerobic exercise capacity decreased exponentially. Also, decrease of sub-maximal aerobic exercise capacity followed increase of altitude increased as high physical fitness level. Men's decreasing ratio bigger than women's decreasing ratio but relative value(decreasing ration/FFM) didn't different men and women. But rest %SpO2 more decreased(p<.05) in women than men in simulated 5,000 m, this phenomenon because to ventilation, oxygen affinity in blood, PO2 effected on %SpO2 in blood, and this factors induced sex difference in extremely altitude. Also, sub-maximal aerobic exercise capacity in one-off exercise at simulated high altitude environment didn't difference between ACE gene polymorphism. KCI Citation Count: 6